Strategi Pembelajaran Aktif dalam Meningkatkan Keterampilan Kritikal Siswa di Era Modern - Muhamad Syafiqul Humam; Muh. Hanif (Pusat Riset dan Inovasi Nasional, 2025)
This research leads to exploring the effectiveness of active learning strategies in improving students' critical thinking skills in the modern era. By utilizing a qualitative approach and field study methods, the research was conducted at SMP IT Mutiara Ilmu Sokaraja. Data was collected through observation, semi-structured interviews, and documentation of principals, teachers, and 8th grade students. The results of the study prove that active learning strategies, such as group discussions, questions and answers, and project-based learning, significantly improve students' critical thinking skills. Students are honed to analyze, evaluate, and solve problems independently, so they are better prepared to face the challenges of the 21st century. In addition, the study reveals the important role of technology as a support for active learning, although its use is still limited to simple devices such as laptops and projectors. The obstacles found include limited technology facilities, learning time, and diverse levels of student readiness. These findings support Neil Smelser's concept of social adaptation, where active learning reflects an adaptive response to modernizing changes in education. The conclusion of this study is that active learning strategies are effective in building students' critical thinking skills, but require support in the form of adequate technological facilities and intensive training for teachers. The implications of this study emphasize the importance of investment in educational technology and teacher capacity building to optimize the implementation of active learning in various educational contexts.